Advanced Forward-Looking Sonar and Imagery Data Processing - Berdnikova, J.; Kozevnikov, V.; Zamarajev, J.; Raja, A. (Elektronika ir Elektrotechnika, 2010)
This paper focuses on a forward-looking sonar prototype, which is the main unit in a complex data acquisition system. The principles and diagrams of the sonar and the corresponding processing algorithms will be described. The goal is to increase forward-looking sonar resolution both by complex amplitude-phase manipulated signals and the sonar imagery data processing. Different real-time processing methods are discussed and modeled. Ill. 10, bibl. 11 (in English; abstracts in English, Russian and Lithuanian).